Laporan Kasus : Anensefali - Fathul Qadir Kasyfi; Welay, Santri Ditira Welay; Bambang Kurniawan (Medula, 2026)
Anencephaly is a fetal development disorder characterized by the absence of skull bones accompanied by a lack of most or all of the fetal brain tissue. Anencephaly is a developmental pathology characterized by a fetus that does not have a calvarium, with a lack of most or all of the fetal brain tissue. The number of cases of anencephaly varies, estimated between 0.5–2 per 1000 births. In some cases anencephaly may be caused by chromosomal abnormalities or involve a single gene defect or disruption of the amniotic membrane. One of the genes related to folate metabolism is believed to play a role in the process of anencephaly, one of which is methylene tetrahydrofolate reductase which has been shown to be associated with the risk of NTDs. The causes of this anencephaly are multifactorial including iatrogenic, toxic, metabolic, nutritional and chromosomal. In this case, a 28-year-old patient, G3P1A1 with a gestational age of 25 weeks came to the Obstetrics Polyclinic with no complaints and wanted to be referred to the fetomaternal department of dr. H. Abdul Moeloek Lampung Province, because he was diagnosed with congenital anencephaly in his fetus. Physical and supporting examinations found fetal movement, fetal heart rate 143x/minute, and USG results showed frog eye appearance and laboratory results obtained reactive Anti-HIV. The diagnosis can be confirmed as anencephaly with HIV. The patient terminated her pregnancy vaginally.